The relationship between the medium of photography and video in constructing people´s identity in Gillian Wearing works (A relação entre o suporte fotográfico e o vídeo na construção da identidade de pessoas nos trabalhos de Gillian Wearing) - Amorim da Silva, Patricia (Aurora. Revista de Arte, Mídia e Política, 2018)
Gillian Wearing (born 1963) is a British artist who got recognition through The Turner Prize in 1997 and exhibitions held all over Europe, United States and Britain. Wearing uses photography and video to share her thoughts and ideas. Her work is characterized as a kind of documentary, which does not intend to be impartial, of the popular culture of her generation in Great Britain using photography and video as a way of registration of people’s thoughts and issue’s about life. More than pictures and video records, her work is meaningful by its action.